Estudo taxonômico de Astyanax Baird & Girard, 1854 e Deuterodon Eigenmann, 1907 (Ostariophysi: Characiformes: Characidae) de três bacias hidrográficas do Estado do Paraná. - Oliveira, Carlos Alexandre Miranda (2011)
A taxonomic study on Astyanax and Deuterodon from hidrografic basins of Paraná State was performed. The Paraná State, despite of densely inhabited, has been poorly studied regarding its ichthyofauna. The scope of this study was correctly identifyingspecies of "lambaris" belonging to those genera, which are very similar to each other. For that, 29 morphometrics and 16 counts were taken from 479 specimens. Analysing recently captured specimens, in addition to comparative material, type specimens and original descriptions, nine species of Astyanax and two of Deuterodon were identified, totalizing 11 valid species. Astyanax altiparanae, A. biotae, A. bockmanni, A. aff. fasciatus, A. aff. paranae, A. paranae and A. schubarti were recognized in the upper Rio Paraná basin. Deuterodon iguape and D. langei occur, respectively, in the Rio Ribeira de Iguape and in coastal basins. Astyanax ribeirae, considered endemic to the Rio Ribeira de Iguape, had its geografic distribution widened to other coastal basins. Astyanax laticeps, until recently identified as A. janeiroensis and restricted to the southern coastal basins of the Paraná State had its geografic distribution broaded to all coastal basins of the State, including the Rio Ribeira de Iguape. On the other hand, the geografic distribution of A. paranae was restricted to the sub-basin of the upper Rio Tibagi. Two species were proposed as new from the upper Rio Paraná basin, besides two from the coastal basin of the Paraná State.